LAYANAN INFORMASI UNTUK MENINGKATKAN PEMAHAMAN TENTANG KARIR BAGI KEPALA KELUARGA KULI PASIR - Ariandi, M. Satriadi; Juli, Sabiruddin; Susanti, Meri; Busihat, Busihat (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aims to determine the success or failure of the information services provided to improve understanding of careers for the head of the sand coolie family in the Pitameh Village Tanjung Saba Nan XX Rt 004 / Rw 001 Lubuk Begalung District Padang City. This research uses the type of Action research. This research was conducted with a two-cycle method. Tools for collecting data are laiseg and observation sheets. Based on observations in this first cycle service, the activeness of the client in participating in information service activities stated in the presentation scale is 33.3% so that the client is categorized in Very Poor evaluation and has not yet gained knowledge new about other work that can be done when the weather conditions are bad, so the next cycle needs to be done. Based on observations during the service delivery process, an increase in client activity was stated in the presentation scale was 83.3% so that the client was categorized in Good rating. Then the results obtained from the two cycles obtained that the implementation of information services was successful.